Ecofisiologia da germinação de sementes de Xyris (Xyridaceae) de campos rupestres - Túlio Gabriel Soares Oliveira (2018)
The genus Xyris (Xyridaceae) presents approximately 100 species widely distributed in the Brazilian campo rupestre. In this work, studies were carried out related to the ecophysiology of the germination of Xyris species typical of campo rupestre. In the first chapter, seeds of three species of Xyris (X. asperula, X. subsetigera and X. trachyphylla) were buried in a naturally occurring area to investigate the occurrence of seasonal cycles of germination and dormancy, and to evaluate in situ longevity of the seeds. For this, the seeds were exhumed every two months and the germination was evaluated over a wide range of constant temperatures. In the second chapter we evaluated the interannual variation in seed germination of a population of X. longiscapa during four consecutive years (2014-2017), in addition to in situ longevity and the occurrence of seasonal dormancy cycles in the seeds produced in 2014. In the third chapter the germination requirements (light and temperature) of six species of Xyris (X. asperula, X. pilosa, X. seubertii, X. subsetigera, X. sp. and X. trachyphylla) were determined. From the germination data, the base temperatures (Tb) and the thermal requirement for the germination of 50% of the seeds (θ50) of four species were calculated. These data, together with the thermal germination range of each species, were used to predict the germinative behavior of the species in the current scenario and in the temperature increase scenarios. Buried seeds of X. asperula, X. longiscapa, X. subsetigera and X. trachyphylla form a persistent seed bank and exhibit seasonal cycles of germination and dormancy. In all species, secondary dormancy is acquired from the middle of the rainy season and overcome during the dry season. Seeds of X. longiscapa collected in 2014 presented a higher degree of dormancy in relation to the other years possibly resulting from effect of the maternal environment. Seeds of Xyris present absolute requirement of light for germination. The thermal germination range and the thermal requirement isvariable among the species. It has been shown that seed germination of X. subsetigera, X. pilosa and X. seubertii are more affected by the higher temperatures, whereas the seeds of X. asperula, X. sp. and X. trachyphylla are more tolerant to temperature increase, not presenting reduction in germination percentage when submitted to higher temperatures.